Analisis Pengaruh Citra Merek, Inovasi Produk Dan Iklan Terhadap Kinerja Pemasaran Melalui Keunggulan Bersaing Sebagai Intervening - Dita Dewi Ramadzan (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2020)
In the current era of globalization, developments in the field of technology are increasingly sophisticated. Smartphones are difficult to separate from activities carried out by humans everyday, there is internet support that makes it easier for humans to connect with anything around the world, social media that makes humans able to communicate with each other over great distances even without meetings.The purpose of this study was to examine and analyze the influence of brand image, product innovation and advertising on the marketing performance of